Kajian Pelaksanaan Pengelolaan dan Pemantauan Dampak Kebisingan di Rumah Sakit “X” Bojonegoro - Muhammad Khilmi Alkhatib; Muhammad Abdus Salam Jawwad (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
Hospital "X" Bojonegoro is obliged to prepare a DELH because it has been operating without environmental documents. Research focuses on measuring noise as a physical parameter. The aim is to determine the noise level in the hospital environment and evaluate the efficiency of management and monitoring of the impact of noise that has been carried out. Noise sampling was carried out on August 6 2024 at four points around "X" Bojonegoro Hospital. Quantitative research uses descriptive analysis and evaluation methods. RKL-RPL is prepared based on Minister of Environment and Forestry Regulation No. P.102/2016. The study in December 2024 used noise sampling data, RKL-RPL matrix reports, and exploratory data. The aim is to complete the hospital's Environmental Evaluation Document. Hospital "X" noise analysis shows levels exceeding standards at the entrance. Mitigation includes a 4 meter brick barrier (29.04 dB(A) reduction) and green open space with Angsana and Trembesi trees (7.2-16 dB absorption). Hospital "X" monitoring shows levels exceeding standards at the entrance. Mitigation includes a 4 meter brick barrier (29.04 dB(A) reduction) and green open space with Angsana and Trembesi trees (7.2-16 dB absorption). Monitoring at 4 points twice a year still shows one point does not meet standards. In accordance with Minister of Environment Decree No. 48/1996, sampling evaluation needs to be carried out every three months.